Joint leisure before and after retirement: A double regression discontinuity approach - Elena G. F. Stancanelli; Arthur van Soest (Institute for the Study of Labor (IZA), 2012)
In the scant literature on partners' joint retirement decisions one of the explanations for joint retirement is externalities in leisure. In this study, we investigate how retirement affects the hours of leisure together of individuals in a couple. Exploiting the law on retirement age in France, we use a regression discontinuity approach to identify the causal effect of retirement on hours of leisure separate and together of individuals in a couple. We find that the retirement probability increases significantly at age 60 for both partners, supporting our identification strategy. We conclude that retirement of the husband significantly increases own hours of leisure of the husband but it does not increase joint leisure hours of the couple. Retirement of the wife increases joint leisure. This asymmetry in responses is well in line with recent literature on joint retirement and suggests that leisure complementarities may not be the main engine of joint retirement.
Keywords: D13; J22; J14; C1; 330; leisure; ageing; retirement; regression discontinuity; Altersgrenze; Ehe; Freizeit; Zeitverwendung; Frankreich